Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine

Orthogonally functionalized donor/acceptor homo- and heterodimeric dyes for dye-sensitized solar cells: an approach to introduce panchromaticity and control the charge recombination - Sil, Manik Chandra; Sudhakar, Vediappan; Kavungathodi, Munavvar Fairoos Mele; Punitharasu, Vellimalai; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Organic dyes possessing conjugated pi-framework forms closely packed monolayers on photoanode in dye-sensitized solar cell (DSSC), because of the limitation to control the orientation and the extend of intermolecular pi-pi interaction, self-aggregation of dyes leads to reduced cell performance. In this report, a series of homodimeric (D-1-D-1, and D-2,-D-2) and heterodimeric (D-1-D-2 and D-2-D-4) donor/acceptor (D/A) dyes containing spiroBiProDOT pi-spacer were designed and synthesized by utilizing Pd-catalyzed direct arylation reaction and correlates the device performance with monomeric dyes (D-1 and D-2). Both the thiophenes (pi-spacer) of spiroBiProDOT were functionalized with same or different donor groups which led to homodimeric and heterodimeric chromophores in a single sensitizer. The homodimeric spirodye D-1-D-1 showed higher power conversion efficiency (PCE), of 7.6% with a V-oc and J(sc) of 0.672 V and 16.16 mA/cm(2), respectively. On the other hand, the monomeric D-1 exhibited a PCE of 3.2% (V-oc of 0.64 V and J(sc) of 7.2 mA/cm(2)); which is lower by 2.4 fold compared to dimeric analogue. The spiro-unit 20 provides flexibility between the incorporated chromophores to orient on TiO2 due to four sp(3)-centers, which arrest the molecular motions after chemisorption. This study shows a new molecular approach to incorporate two chromophores in the dimeric dye possessing complementary absorption characteristics toward panchromatic absorption. The attenuated charge recombination at TiO2/Dye/redox couple interface in case of D-1-D-1, owing to better passivation of TiO2 surface, was elucidated through impedance analysis. The FT-IR spectrum of D,-D, adsorbed on TiO2 film indicated both the carboxylic units were involved in chemisorption which makes strong coupling between dye and TiO2.

Self-assembly of Cis-configured squaraine dyes at the TiO2-dye interface: far-red active dyes for dye-sensitized solar cells - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2018)
To synergize both steric and electronic factors in designing the dyes for dye-sensitized solar cells, a series of cis-configured unsymmetrical squaraine dyes P11-P15 with suitably functionalized alkyl groups and squaric acid units containing the electron-withdrawing groups were synthesized, respectively. These dyes capture the importance of (i) the effect and position of branched alkyl groups, (ii) mono- and di-anchoring groups containing dyes, and (iii) further appending the alkyl groups through the cyanoester vinyl unit on the central squaric acid units of DAD-based cis-configured squaraine dyes. All the above factors govern the controlled self-assembly of the dyes on the TiO2 surface which helps to broaden the absorption profile of the dyes with an increased energy-harvesting process. With respect to the position of the branched alkyl groups, dye P11 with the sp(3)-C and N-alkyl groups away from the TiO2 surface showed a better device efficiency of 5.98% (J(sc) of 14.46 mA cm(-2), V-oc of 0.576 V, and ff of 71.8%) than its positional isomer P12 with 3.45% (J(sc) of 8.78 mA cm(-2), V-oc of 0.554 V, and ff of 70.9%). However, with respect to the dyes containing mono- and di-anchoring groups, P13 with two anchoring units exhibited a superior device performance of 7.58% (J(sc) of 17.12 mA cm(-2), V-oc of 0.618 V, and ff of 71.7%) in the presence of optically transparent co-adsorbent CDCA (3 alpha,7 alpha-dihydroxy-5 beta-cholanic acid) than dyes P11 and P12.

pi-Extended cis-configured unsynimetrical squaraine dyes for dye-sensitized solar cells: panchromatic response - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Singh, Ambarish Kumar; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2019)
{Light absorbing sensitizer is the heart of the third generation photovoltaic technologies such as dye sensitized solar cells. Despite possessing large extinction coefficients for the metal-free organic dyes, the light harvesting efficiency is limited with the narrow absorption 20 profile in either visible or NIR regions of the solar spectrum. Though monolayer formation of organic sensitizers on semiconducting metal oxide surface leads to dye-dye interaction that leads to broadening the absorption profile, the contribution of the aggregated state to the power conversion process is found out to be poor. Here, we have engineered far-red active pi-extended cis-configured unsymmetrical squaraine dyes with carboxylic acid and cycnoacetic acid as anchoring groups with controlled aggregation and panchromatic light absorption by including the steric and electronic factors. The presence of sp(3)-C (out-of-plane) and N-alkyl (in-plane) groups played an important role in modulating the assembly of the dyes on the TiO2 electrode; the cis-squaraine unit helps to extend the conjugation in the NIR region besides enhancing the visible transition and the incident photon-to-current conversion efficiency profile that showed the importance of anchoring groups for the panchromatic response. Dye PSQ10 showed solar-to electric conversion with an onset of 850 nm with the device performance of 7.0% (V-oc = 0.581 V, J(sc) = 17.06 mA/cm(2)
Keywords: cis-squaraine dyes; Dye aggregation; Dye-sensitized solar cells; extended far-red absorption; panchromatic response